A method for improving the corrosion resistance of grey cast iron parts

By performing secondary annealing of gray cast iron parts under a protective atmosphere, a dense SiO2 oxide film is formed, which solves the problem of insufficient corrosion resistance of gray cast iron parts in the prior art, and achieves improving corrosion resistance in industrial production while taking into account environmental protection requirements.

CN114214491BActive Publication Date: 2025-03-14JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111587977.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-23
Publication Date
2025-03-14
Estimated Expiration
2041-12-23

AI Technical Summary

Technical Problem

The prior art is difficult to improve the corrosion resistance of gray cast iron parts while meeting industrial production, while taking into account environmental protection requirements.

Method used

By performing a secondary annealing treatment in a protective atmosphere, a first annealing is performed in high purity hydrogen to remove surface carbon, and then a second annealing is performed in high purity argon to form a dense SiO2 oxide film.

Benefits of technology

This method significantly improves the corrosion resistance of gray cast iron parts, solves the problem that the existing technology cannot meet both industrial production and environmental protection requirements, and at the same time reduces costs, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114214491B_ABST
    Figure CN114214491B_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the corrosion resistance of gray cast iron parts. The method is carried out by subjecting the gray cast iron parts to a two-step heat treatment process, firstly removing C near the surface of the cast iron parts by high-temperature heat treatment, and then heat treating at a lower temperature to make Si inside the cast iron segregate to the surface and react with residual O2 in the heat treatment atmosphere H2, and generate a SiO2 protective layer on the surface of the parts, thereby forming a SiO2 adhesion film on the surface of the cast iron alloy. The film is continuous, dense, stable and has a high melting point, which can effectively prevent the base metal from being corroded by water, and the process flow is relatively simple, low in cost, can meet the needs of industrial production, is environmentally friendly and pollution-free, effectively improves the water corrosion resistance of gray cast iron and its products, greatly reduces the huge losses caused by the corrosion of cast iron by water vapor in the environment in industry, and has broad market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion treatment of metal composites, and in particular to a method for improving the corrosion resistance of grey cast iron parts. Background Art

[0002] Corrosion is a common problem that occurs when metal materials are used. Metal materials are damaged by the surrounding medium, which significantly reduces the strength, plasticity, toughness and other mechanical properties of metal materials. It also deteriorates the electrical and optical physical properties of metal components and shortens the service life of equipment. Corrosion is more common in the automotive industry, because a large number of parts are made of cast iron, and gray cast iron is the most widely used among cast irons. Gray cast iron parts are easily corroded or rusted due to the interaction with the surrounding medium.

[0003] Every year, my country's automobiles suffer losses of 100 billion yuan due to corrosion, among which cast iron corrosion is the most serious. At room temperature, cast iron will absorb water vapor on its surface in the air to form a thin water film, in which gases such as O2 dissolve, making it an electrolyte. With this layer of electrolyte, the iron and cementite on the surface of the cast iron form two electrodes due to the high and low electric potential, with iron as the anode (negative electrode) and cementite as the cathode (positive electrode), forming countless tiny primary batteries. At room temperature, when the aqueous solution on the surface of the cast iron is acidic, iron and water react with hydrogen to eventually generate hydrogen and Fe2O3; at room temperature, when the aqueous solution is neutral or weakly acidic, iron, water and O2 react with oxygen absorption to eventually generate rust Fe2O3, affecting its further processing and production. With the increase in metal production and the development of industry, this economic loss has a tendency to gradually increase, so it is necessary to carry out research on the corrosion resistance of gray cast iron at room temperature to reduce economic losses.

[0004] In order to solve the above problems, the current industrial production generally uses a method of adding one or more elements such as Al, Cr, Ti, Ni, etc. to cast iron to form a complex to improve the corrosion resistance of cast iron at room temperature, thereby increasing the utilization rate of cast iron. However, since the large-scale use of these alloy elements will affect its own performance, such as reduced electrical conductivity and thermal conductivity and affected mechanical properties, the use of this process is limited and is not suitable for actual industrial production. For this reason, the commonly used metal surface anti-corrosion methods currently include baking, galvanizing, surface coating, etc.

[0005] However, although these methods have good anti-corrosion effects, they also have many shortcomings. For example, the galvanizing process will cause great environmental pollution, which does not meet environmental protection requirements; in addition, if the pretreatment before galvanizing is not thorough, oxide film artifacts will appear on the surface, which will affect the normal deposition of zinc; when the temperature is too high, the coating is easy to turn white and orange peel, and when the temperature is too low, the paint layer is easy to flow, which has a negative impact on the quality of the metal surface coating. Summary of the invention

[0006] 1. Technical problems to be solved

[0007] The purpose of the present invention is to solve the problem that the methods in the prior art cannot meet the requirements of environmental protection while satisfying industrial production, and to propose a method for improving the corrosion resistance of grey cast iron parts.

[0008] 2. Technical solution

[0009] In order to achieve the above object, the present invention adopts the following technical solutions:

[0010] A method for improving the corrosion resistance of grey cast iron parts, comprising the following steps:

[0011] Step 1: Polish the surface of the gray cast iron parts with sandpaper to remove the oxide film;

[0012] Step 2: Place the polished gray cast iron parts in acetone and ethanol for ultrasonic cleaning in turn to remove surface oil and fine impurity particles, then place the ultrasonically cleaned alloy in electrolyte for electrolytic polishing, and then use ethanol ultrasonic cleaning again;

[0013] Step 3: The gray cast iron parts are kept at 1200° C. for 1 hour in a tube furnace with high-purity hydrogen (purity 99.9999%), and then cooled with the furnace, and the hydrogen is dried with silica gel before entering the tube furnace;

[0014] Step 4: The parts in step 3 are then kept at 1000°C for 12 hours in the presence of high-purity argon gas (purity 99.9999%), and then cooled in the furnace.

[0015] Preferably, the basic parameters of the grey cast iron parts in step 1 are: HT250, HB:203-205, which contain 3.49% carbon, 0.072% sulfur, 2.11% silicon, 0.65% manganese and 0.037% phosphorus.

[0016] Preferably, in step 2, the electrolytic polishing adopts a Zhaoxin constant current source with an output current of 0-5A and a stability of ≤0.1%+3mA. The polishing liquid is a mixture of perchloric acid and acetic acid. The gray cast iron automotive parts are placed in the anode, and cathode copper plates are placed on the left and right sides. A preset current is passed and the polishing time is 20-60s.

[0017] Preferably, steps 2, 3 and 4 also include a purge step before annealing, specifically placing the parts to be annealed in a sealed environment and pumping the pressure to no more than -0.1 atm, and then introducing an inert protective gas.

[0018] Preferably, the gas flow rate of the high-purity hydrogen or high-purity argon introduced during the annealing treatment in steps 2, 3 and 3 is 90 ml / min-150 ml / min.

[0019] Preferably, the annealing process in steps 2, 3 and 4 is carried out at room temperature for 2 hours.

[0020] Preferably, the annealing process in steps 2, 3 and 4 is carried out for 3-4 hours before the temperature is raised to the required annealing temperature.

[0021] Preferably, in step 1, a metallographic grinder is used to grind the upper and lower surfaces of the component, and the sandpaper used is 600 mesh, 1000 mesh, 2000 mesh, 3000 mesh, 5000 mesh and 7000 mesh, respectively.

[0022] 3. Beneficial effects

[0023] Compared with the prior art, the advantages of the present invention are:

[0024] (1) In the present invention, the gray cast iron is subjected to a secondary annealing treatment under a protective atmosphere. First, the first annealing is performed. After annealing at 1200°C for 1 hour, the C on the surface of the cast iron segregates to the surface and reacts with hydrogen to form CH4 gas which is discharged with the tail gas, thereby greatly reducing the C content in the shallow surface layer of the cast iron after the first annealing, thereby eliminating the interference of the surface C on the diffusion of Si to the surface layer. Then, the second annealing is performed to diffuse Si to the surface and be fully oxidized so that the oxide film is formed more uniformly and densely, thereby further improving its corrosion resistance.

[0025] (2) In the present invention, the process is easy to repeat, low in cost, environmentally friendly and pollution-free, and can meet the needs of industrial production. It effectively improves the corrosion resistance of gray cast iron parts and solves the problem that the existing method for improving the water corrosion resistance of gray cast iron parts at room temperature cannot meet the requirements of industrial production while also meeting environmental protection requirements.

[0026] (3) In the present invention, this method can effectively prevent gray cast iron parts from being corroded by water vapor in the air at room temperature, greatly reducing the huge losses caused by water corrosion of gray cast iron parts in industry, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the XPS spectrum of the annealed grey cast iron component in Example 13 of the present invention;

[0028] Figure 2 The annealed surface of the gray cast iron component that has not been annealed in Example 13 of the present invention;

[0029] Figure 3 The annealed surface of the gray cast iron component after annealing in Example 13 of the present invention;

[0030] Figure 4 The cross section of the grey cast iron component that has not been annealed in Example 13 of the present invention;

[0031] Figure 5 The cross section of the annealed grey cast iron component in Example 13 of the present invention;

[0032] Figure 6 It is a diagram of a grey cast iron component dripping water without annealing and after annealing in Example 13 of the present invention;

[0033] Figure 1 In (a), the binding energy of the Si 2p orbital is 102.16 eV, which is close to the standard binding energy of the Si 2p orbital in SiO2, 103.5 eV. This indicates that SiO2 exists in the surface film of the material.

[0034] Figure 1 In (b), for the O1s orbital, its binding energy is 530.1 eV, which is consistent with the standard binding energy of O 1s in SiO2, 531.2 eV. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0036] A method for improving the corrosion resistance of grey cast iron parts, comprising the following steps:

[0037] Step 1: Polish the surface of the gray cast iron parts with sandpaper to remove the oxide film;

[0038] Step 2: Place the polished gray cast iron parts in acetone and ethanol for ultrasonic cleaning in turn to remove surface oil and fine impurity particles, then place the ultrasonically cleaned alloy in electrolyte for electrolytic polishing, and then use ethanol ultrasonic cleaning again;

[0039] Step 3: The gray cast iron parts are kept at 1200° C. for 1 hour in a tube furnace with high-purity hydrogen (purity 99.9999%), and then cooled with the furnace, and the hydrogen is dried with silica gel before entering the tube furnace;

[0040] Step 4: The parts in step 3 are then kept at 1000°C for 12 hours in the presence of high-purity argon (purity 99.9999%), and then cooled in the furnace.

[0041] In the embodiment of the present invention, the secondary annealing treatment of the gray cast iron parts is carried out at a temperature of 800°C-1000°C. According to the Ellingham diagram, Si has a high affinity for oxygen. It first reacts with the residual O2 in the H2 of the annealing atmosphere to generate SiO2, thereby forming a SiO2 composite adhesion film on the surface of the gray cast iron parts. The film is dense, stable and has a high melting point, which can effectively prevent the base metal from being corroded.

[0042] In the embodiment of the present invention, and Si 4+ The ionic radius is 0.041nm, Fe 2+ The radius is 0.075nm. The oxide lattice constant formed by the Si element is small, and it is relatively difficult for the matrix metal ions to diffuse through it, thereby greatly improving the corrosion resistance of gray cast iron parts.

[0043] The method for improving the corrosion resistance of gray cast iron parts provided by the present invention has a simple process flow, is environmentally friendly and pollution-free, and significantly improves the corrosion resistance of gray cast iron, because Si has a higher affinity for oxygen than Fe, and the trace element Si in the cast iron parts preferentially reacts with the residual O2 atmosphere in the H2 gas under annealing conditions to form a stable non-metallic protective film. Cast iron is the most consumed metal in industrial production, and the gray cast iron obtained by this method can ensure corrosion resistance.

[0044] As another preferred embodiment of the present invention, the first annealing treatment is to heat to an annealing temperature of 600°C-1000°C in an annealing atmosphere, keep the temperature for 720min-1440min, and then cool to room temperature.

[0045] As another preferred embodiment of the present invention, the annealing temperature in step 3 is 1100°C.

[0046] As another preferred embodiment of the present invention, the cooling time in step 3 is 1440 minutes.

[0047] As another preferred embodiment of the present invention, the gas flow rate of hydrogen introduced in step 3 is 90 ml / min-150 ml / min. Specifically, H2 gas (containing about 5×10 2 Pa oxygen).

[0048] As another preferred embodiment of the present invention, the annealing holding time in step 3 is 2 hours.

[0049] As another preferred embodiment of the present invention, in step 3, the annealing atmosphere is selected to be a mixture of argon and hydrogen, wherein the hydrogen accounts for 20%.

[0050] As another preferred embodiment of the present invention, the electrolytic polishing in step 2 is intended to remove residual stress and make the surface brighter.

[0051] As another preferred embodiment of the present invention, in the method for improving the water corrosion resistance of gray cast iron parts at room temperature, the method further includes drying the gas with a mixture of silica gel and molecular sieve before the gas passes through the tube furnace in step 3, wherein the silica gel accounts for 80% by weight.

[0052] As another preferred embodiment of the present invention, the polishing in step 1 is performed by grinding with sandpaper to 3000 mesh, or vibration polishing can be used for 1 hour; the electrolyte for electrolytic polishing is a mixture of perchloric acid and acetic acid, and the volume ratio of perchloric acid to acetic acid is (1-3): (9-7).

[0053] As another preferred embodiment of the present invention, in the method for improving the room-temperature water corrosion resistance of gray cast iron parts, it also includes a gas washing step before the annealing treatment in steps 3 and 4, specifically, the gray cast iron parts are placed in a sealed environment (generally, they are placed in a quartz boat, and then the arranged quartz boat is placed in the constant temperature zone of a tube furnace) and evacuated to a pressure not greater than -0.1atm, and then an inert protective gas is introduced to normal atmospheric pressure, which is generally repeated 3-5 times. After the last gas washing and vacuuming, H2 is introduced to a pressure slightly higher than the standard atmospheric pressure to prevent backflow during ventilation.

[0054] As another preferred embodiment of the present invention, the inert protective gas can be helium, neon, argon, krypton, xenon, radon, etc., which can be selected according to the specific needs and is not limited here. Here, preferably, the inert protective gas introduced is argon.

[0055] An embodiment of the present invention also provides a cast iron product prepared by using the above method for improving the corrosion resistance of grey cast iron parts.

[0056] The embodiment of the present invention also provides an application of the method for improving the corrosion resistance of iron-based parts in the corrosion protection of iron products and / or gray cast iron products. For example, it can be the corrosion protection of gray cast iron parts.

[0057] As another preferred embodiment of the present invention, compared with the common practice of adding one or more elements such as Al, Cr, Ti, Ni to cast iron to form a composite to improve the corrosion resistance and thus increase the utilization rate of Fe in current industrial production, the present invention improves the corrosion resistance of gray cast iron parts by using secondary annealing treatment on gray cast iron parts, and forms a Fe-SiO2 composite attachment film on the alloy surface by pretreatment or annealing at a higher temperature in H2 gas. The formed SiO2 protective film is dense, stable and has a high melting point, which can effectively prevent the base metal from being corroded by water. Moreover, the electrical conductivity, thermal conductivity and mechanical properties are less affected.

[0058] The technical effect of the method for improving the corrosion resistance of grey cast iron parts of the present invention is further described below by listing specific embodiments.

[0059] Example 1

[0060] A method for improving the water corrosion resistance of gray cast iron parts at room temperature comprises the following steps:

[0061] Step 1: Polish the surface of the gray cast iron parts with sandpaper to remove the oxide film;

[0062] Step 2: Place the polished gray cast iron parts in acetone and ethanol for ultrasonic cleaning in turn to remove surface oil and fine impurity particles, then place the ultrasonically cleaned alloy in electrolyte for electrolytic polishing, and then use ethanol ultrasonic cleaning again;

[0063] Step 3: Keep the gray cast iron parts in a tube furnace with high-purity hydrogen (purity 99.9999%) at 1200°C for 1 hour, and then cool them down with the furnace. The hydrogen is dried with silica gel before entering the tube furnace;

[0064] Step 4: The parts in step 3 are then kept at 1000°C for 4 hours in a chamber filled with high-purity argon (purity 99.9999%), and then cooled in the furnace;

[0065] Example 2

[0066] Compared with Example 1, except that the holding time in step 2 is 2 hours, the rest is the same as Example 1.

[0067] Example 3

[0068] Compared with Example 1, except that the holding time in step 2 is 4 hours, the rest is the same as Example 1.

[0069] Example 4

[0070] Compared with Example 1, except that the insulation time in step 2 is 8 hours, the rest is the same as Example 1.

[0071] Example 5

[0072] Compared with Example 1, except that the insulation time in step 2 is 16 hours, the rest is the same as Example 1.

[0073] Example 6

[0074] Compared with Example 1, except that the insulation time in step 2 is 32 hours, the rest is the same as Example 1.

[0075] Example 7

[0076] A method for improving the corrosion resistance of iron-based parts, comprising the following steps:

[0077] Step 1: Polish the surface of the gray cast iron parts with sandpaper to remove the oxide film;

[0078] Step 2: Place the polished gray cast iron parts in acetone and ethanol for ultrasonic cleaning in turn to remove surface oil and fine impurity particles, then place the ultrasonically cleaned alloy in electrolyte for electrolytic polishing, and then use ethanol ultrasonic cleaning again;

[0079] Step 3: Keep the gray cast iron parts in a tube furnace with high-purity hydrogen (purity 99.9999%) at 1200°C for 1 hour, and then cool them down with the furnace. The hydrogen is dried with silica gel before entering the tube furnace;

[0080] Step 4: Then, the parts in step 3 are kept at 1000° C. for 4 hours in a high-purity argon-hydrogen mixed gas (hydrogen 20%), and then cooled in the furnace;

[0081] Example 8

[0082] A method for improving the water corrosion resistance of grey cast iron parts, comprising the following steps:

[0083] Step 1: Polish the surface of the gray cast iron parts with sandpaper to remove the oxide film;

[0084] Step 2: Place the polished gray cast iron parts in acetone and ethanol for ultrasonic cleaning in turn to remove surface oil and fine impurity particles, then place the ultrasonically cleaned alloy in electrolyte for electrolytic polishing, and then use ethanol ultrasonic cleaning again;

[0085] Step 3: Keep the gray cast iron parts in a tube furnace with high-purity hydrogen (purity 99.9999%) at 1200°C for 1 hour, and then cool them down with the furnace. The hydrogen is dried with silica gel before entering the tube furnace;

[0086] Step 4: Then, the parts in step 3 are kept at 1000° C. for 4 hours in a high-purity argon-hydrogen mixed gas (hydrogen 20%), and then cooled in the furnace;

[0087] Example 9

[0088] A method for improving the corrosion resistance of grey cast iron parts, comprising the following steps:

[0089] Step 1: Polish the surface of the gray cast iron parts with sandpaper to remove the oxide film;

[0090] Step 2: Place the polished gray cast iron parts in acetone and ethanol for ultrasonic cleaning in turn to remove surface oil and fine impurity particles, then place the ultrasonically cleaned alloy in electrolyte for electrolytic polishing, and then use ethanol ultrasonic cleaning again;

[0091] Step 3: Keep the gray cast iron parts in a tube furnace with high-purity hydrogen (purity 99.9999%) at 1200°C for 2 hours, and then cool them down with the furnace. The hydrogen is dried with silica gel before entering the tube furnace;

[0092] Step 4: Then, the parts in step 3 are kept at 1000° C. for 4 hours in a high-purity argon-hydrogen mixed gas (hydrogen 20%), and then cooled in the furnace;

[0093] Example 10

[0094] Compared with Example 9, except that the insulation time in step 4 is 8 hours, the rest is the same as Example 9.

[0095] Embodiment 11

[0096] Compared with Example 9, except that the insulation time in step 4 is 12 hours, the rest is the same as Example 9.

[0097] Example 12

[0098] Compared with Example 9, except that the insulation time in step 4 is 16 hours, the rest is the same as Example 9.

[0099] Embodiment 13

[0100] Compared with Example 9, except that the insulation time in step 4 is 20 hours, the rest is the same as Example 9.

[0101] Embodiment 14

[0102] Compared with Example 9, except that the insulation time in step 4 is 24 hours, the rest is the same as Example 9.

[0103] Embodiment 15

[0104] Compared with Example 9, except that the insulation time in step 4 is 28 hours, the rest is the same as Example 9.

[0105] Example 16

[0106] Compared with Example 9, except that the electrolyte for electrolytic polishing in step 2 is a mixture of perchloric acid and acetic acid, and the volume ratio of perchloric acid to acetic acid is 2:7, the rest is the same as Example 9.

[0107] Embodiment 17

[0108] Compared with Example 9, except that the electrolyte for electrolytic polishing in step 2 is a mixture of perchloric acid and acetic acid, and the volume ratio of perchloric acid to acetic acid is 2:6, the rest is the same as Example 9.

[0109] Embodiment 18

[0110] Compared with Example 9, except that the electrolyte for electrolytic polishing in step 2 is a mixture of perchloric acid and acetic acid, and the volume ratio of perchloric acid to acetic acid is 3:7, the rest is the same as Example 9.

[0111] Embodiment 19

[0112] Compared with Example 9, except that the electrolyte for electrolytic polishing in step 2 is a mixture of perchloric acid and acetic acid, and the volume ratio of perchloric acid to acetic acid is 2:9, the rest is the same as Example 9.

[0113] In the present invention, experimental analysis is performed on the above embodiments, and the following conclusions are obtained:

[0114] See also Figure 1 (a) and Figure 1 (b) XPS characterization of the annealed grey cast iron parts in Example 13 of the present invention, specifically, surface element detection using a photoelectron spectrometer (XPS). Figure 1 (a) is the XPS analysis of Si 2p orbital, with a peak value of 102.16 eV. Figure 1 (b) is the XPS analysis diagram of the O1s orbital. The peak value is 530.1eV, and the corresponding binding energy is consistent with the binding energy of SiO2, so the alloy surface is considered to be SiO2.

[0115] See also Figure 2 and Figure 3The SEM and element distribution diagrams of the surface of the unannealed gray cast iron component and the annealed surface of the annealed gray cast iron component in Example 13 of the present invention are shown. It can be seen that the surface of the annealed gray cast iron component is smooth and the Si and O signals are significant, while the Fe signal is relatively weak.

[0116] See also Figure 4 and Figure 5 The cross-section characterization SEM images and element distribution diagrams of the gray cast iron parts that have not been annealed and the gray cast iron parts that have been annealed in Example 13 of the present invention are shown respectively. It can be seen that the Si element and the O element do not aggregate near the alloy surface of the parts that have not been annealed, and no oxide film is formed. However, it can be seen that the Si element and the O element have obvious aggregation near the alloy surface of the gray cast iron parts after annealing, forming a continuous and dense SiO2 oxide film, which can effectively prevent the gray cast iron and its products from being corroded at room temperature.

[0117] See also Figure 6 The figure shows the gray cast iron parts dripping water without annealing and after annealing in Example 13 of the present invention. It can be seen from the figure that the sample without annealing has obvious rust phenomenon, but the sample after annealing still maintains the original morphology and does not rust. It proves that the present invention effectively improves the corrosion resistance of gray cast iron parts.

[0118] In the above embodiments of the present invention, in order to solve the problems raised in the background technology, a method for improving the corrosion resistance of gray cast iron parts is provided based on Wanger theory by forming a composite oxide film on the surface of gray cast iron parts containing added trace elements Si, thereby improving the room temperature water corrosion resistance of the gray cast iron parts.

[0119] The prepared sample is placed in a tubular furnace, and H2 atmosphere is introduced as a protective gas for secondary annealing. Si has a high affinity for O, and it first reacts with the residual O2 in the annealing atmosphere H2 to generate SiO2, thereby forming a SiO2 adhesion film on the surface of the FeSi alloy, which can effectively prevent the gray cast iron and its products from being corroded by water at room temperature, greatly reducing the huge losses caused by water corrosion of cast iron in industry.

[0120] The method for improving the corrosion resistance of iron-based parts provided by the present invention meets the requirement of reducing costs in industrial production and can meet the needs of industrial production development. In addition, cast iron is cheap and widely used, and gray cast iron accounts for more than 80% of the total output of cast iron. It has low cost, low price and wide application. It is mainly used for machine tool bed, gear box, pulley, base, cylinder body, cover, hand wheel and other parts with low force, wear resistance and shock absorption.

[0121] That is, the gray cast iron parts of the present invention have higher performance stability after secondary annealing, and are suitable for use in special environments. The improvement lies in that a SiO2 adhesion film is formed on the surface of the cast iron by pretreatment or annealing at a higher temperature in H2 gas. The formed SiO2 protective film is dense, stable and has a high melting point, which can effectively prevent the base metal from being oxidized. And Si 4+ The ionic radius is 0.041nm, Fe 2+ The radius is 0.075nm. The oxide lattice constant formed by Si element is small, and it is relatively difficult for metal-based ions to diffuse through it, which greatly improves the corrosion resistance of gray cast iron parts.

[0122] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for improving the corrosion resistance of gray cast iron parts, characterized in that: The following steps are involved: Step 1: Polish the surface of the gray cast iron parts with sandpaper to remove the oxide film; Step 2: Place the polished gray cast iron parts in acetone and ethanol for ultrasonic cleaning in turn to remove surface oil and fine impurity particles, then place the ultrasonically cleaned alloy in electrolyte for electrolytic polishing, and then use ethanol ultrasonic cleaning again; Step 3: Keep the gray cast iron parts at 1200°C for 1 hour in a tube furnace with high-purity hydrogen (purity 99.9999%), then cool them with the furnace, and dry them with silica gel before the hydrogen enters the tube furnace; Step 4: The parts in step 3 are then kept at 1000°C for 12 hours in a furnace filled with high-purity argon (purity 99.9999%), and then cooled; The basic parameters of the gray cast iron parts in step 1 are: HT250, HB:203-205, which contains 3.49% carbon, 0.072% sulfur, 2.11% silicon, 0.65% manganese, and 0.037% phosphorus. The electrolytic polishing in step 2 adopts Zhaoxin constant current source, the output current is 0-5 A, and the stability is ≤ 0.1%+3 mA, the polishing liquid is a mixture of perchloric acid and acetic acid, the gray cast iron automobile parts are placed in the anode, the cathode copper plates are placed on the left and right sides, a preset current is passed, and the polishing time is 20-60s, and the steps 3 and 4 also include a step of washing before annealing, specifically placing the parts to be annealed in a sealed environment and evacuating to a pressure of no more than -0.1atm, and then passing inert protective gas, the gas flow rate of high-purity hydrogen or high-purity argon passed during the annealing process in the steps 3 and 4 is 90ml / min-150ml / min, the heat is kept at room temperature for 2 hours before the annealing process in the steps 3 and 4, and the temperature is raised to the required annealing temperature after 3-4 hours during the annealing process in the steps 3 and 4.

2. A method for improving the corrosion resistance of grey cast iron parts according to claim 1, characterized in that: In the step 1, a metallographic grinder is used to grind the upper and lower surfaces of the parts, and the sandpaper used is 600 mesh, 1000 mesh, 2000 mesh, 3000 mesh, 5000 mesh and 7000 mesh, respectively.

Citation Information

Patent Citations

  • Method for improving oxidation resistance of magnesium

    CN112662905A

  • Method for improving anti-oxidation capacity of iron-based automobile part

    CN112746150A